2020
DOI: 10.1021/acs.biomac.0c00478
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Size and Cross-Linking Density of Microgels on Cellular Uptake and Uptake Kinetics

Abstract: The unique pH and temperature responsiveness of PNIPAM-based microgels make them a promising target for novel biomedical applications such as cellular drug delivery systems. However, we lack a comprehensive understanding of how the physicochemical properties of microgels relate to their interaction with cells. Here, we show that HEK293T cells take up PNIPAMbased microgels on a second-to-minute time scale. Uptake rates are determined by microgel size and cross-linker content. Using fluorescence confocal live-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 66 publications
2
40
0
Order By: Relevance
“…It is, for example, well known that nanogels can penetrate through pores that are much smaller than the nanogels diameter and even very large microgels can be taken up by cells if they have a low cross linker content. [ 53–56 ]…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is, for example, well known that nanogels can penetrate through pores that are much smaller than the nanogels diameter and even very large microgels can be taken up by cells if they have a low cross linker content. [ 53–56 ]…”
Section: Figurementioning
confidence: 99%
“…It is, for example, well known that nanogels can penetrate through pores that are much smaller than the nanogels diameter and even very large microgels can be taken up by cells if they have a low cross linker content. [53][54][55][56] The concept of zeta-potential is not well-defined for soft objects as charged groups as well as their counter-ions can be distributed inside the object. Despite the fact that models for soft, penetrable charged objects have been developed, [57] one should rather report electrophoretic mobilities instead of zeta-potential, which are calculated using models for rigid nanoparticles with a sharp surface.…”
Section: Doi: 101002/smll202002162mentioning
confidence: 99%
“…Charged microgels had fast cellular uptake, in the range of seconds to minutes. Microgels that were larger than 800 nm in diameter and had cross-linking densities of 10–15 mol% could not be translocated into cells [160] .…”
Section: Attributes Of Man-made Nanomaterials That Affect Endocytosismentioning
confidence: 99%
“…For example, microgels with cross-linking densities between 1.7 and 15 mol% were internalized into cells through several mechanisms, which result in high uptake rates [159] . In another study, poly( N -isopropylacrylamide)-based microgels were used to investigate the effects of nanoparticles with different cross-linking densities on interaction with the plasma membrane [160] Microgels with low cross-linking densities were softer than those with high cross-linking densities. Charged microgels had fast cellular uptake, in the range of seconds to minutes.…”
Section: Attributes Of Man-made Nanomaterials That Affect Endocytosismentioning
confidence: 99%
“… 16 More recently, Switacz et al found that depending on the size and softness of the polymer, the HEK293T cells could take up PNIPAm based microgels. 31 Additionally, a correlation of protein adsorption of ECM of cells and the water content of the grafted PNIPAm brushes was investigated. 34 Even though these recent reveals could be the partial determinant for cell-sheet detachment, to fully apply the advantages of functional substrates for cell-sheet harvesting, systematic and consistent evaluation of cell–substrate and cell–cell adhesion on a well-characterized PNIPAm surface is required.…”
Section: Introductionmentioning
confidence: 99%